Spore-FP1 tuberculosis mucosal vaccine candidate is highly protective in guinea pigs but fails to improve on BCG-conferred protection in non-human primates - White, Andrew D.; Tran, Andy C.; Sibley, Laura; Sarfas, Charlotte; Morrison, Alexandra L.; Lawrence, Steve; Dennis, Mike; Clark, Simon; Zadi, Sirine; Lanni, Faye; Rayner, Emma; Copland, Alastair; et al. (Frontiers in Immunology, 2023)
Tuberculosis remains a major health threat globally and a more effective vaccine than the current Bacillus Calmette Guerin (BCG) is required, either to replace or boost it. The Spore-FP1 mucosal vaccine candidate is based on the fusion protein of Ag85B-Acr-HBHA/heparinbinding domain, adsorbed on the surface of inactivated Bacillus subtilis spores. The candidate conferred significant protection against Mycobacterium. tuberculosis challenge in naïve guinea pigs and markedly improved protection in the lungs and spleens of animals primed with BCG. We then immunised rhesus macaques with BCG intradermally, and subsequently boosted with one intradermal and one aerosol dose of Spore-FP1, prior to challenge with low dose aerosolised M. tuberculosis Erdman strain. Following vaccination, animals did not show any adverse reactions and displayed higher antigen specific cellular and antibody immune responses compared to BCG alone but this did not translate into significant improvement in disease pathology or bacterial burden in the organs.